Experimental evaluation of temperature distribution in armature of a brushed dc machine using thermal imaging - Mohd Azri Hizami, Rasid; Muhammad Nor Azril, Zulkafli; Daing Mohamad Nafiz, Daing Idris; Nurul Fatimah, Abdullah (Institute of Electrical and Electronics Engineers Inc., 2022)
Monitoring the temperature on a rotating armature is necessary to ensure that the maximum temperature permissible by the conductor's insulation class is not exceeded. In a brushed dc machine, the closest location in direct contact with the armature that can be instrumented using thermocouples are the brush and bearing. However, the temperature measured is lower compared to the armature temperature. This paper presents an evaluation on the temperature distribution of an armature of a 250W brushed DC machine using thermal imaging. Using the blocked-rotor test, the temperature was raised to a steady state temperature. The thermal images are taken on the then unmounted armature winding. The temperature distribution was analyzed by identifying the maximum, minimum, and average temperature of each component. The winding, the brush, the armature core, and the commutator are the hottest components. Non-homogenous components, especially the commutator exhibits large temperature range.